Assesment of macroeconomic effects of policies and measures to accelerate the transition to low -carbon development pathway - Ayashev, K. (Nazarbayev University, 2014)
Kazakhstan, former Soviet Socialistic Republic, demonstrates impressive economic growth rates, approximately 10 % annually in 2000-2007 and 7.5 % in 2010-2011. During last years Kazakhstan moved from lower middle income to upper middle income countries group. It is expected that by 2015 Kazakhstan will be classified as a high income country with 15 000 $ GDP per capita level.
Keywords: macroeconomic effects; low-carbon; development pathway